Why is the legalization of euthanasia a badly reasoned and dangerous idea? - Ošlaj, Borut (Anali PAZU HD, 2022)
The article critically analyzes some of the most influential attempts to justify the legalization of euthanasia. Through a careful analysis of the basic arguments presented by Singer and Harris, we show why their defense of euthanasia is badly reasoned. In the second part, we briefly present some of the most probable dangers that any legalization of euthanasia could bring with them. Finally, the special importance of palliative medicine and the need to preserve respect for life and humanity are highlighted.